Introducing the Care Certificate evaluation (innovative practice) - Argyle, Elaine; Thomson, Louise; Arthur, Antony; Maben, Jill; Schneider, Justine M.; Wharrad, Heather (SAGE, 2017)
Although investment in staff development is a prerequisite for high quality and innovative care, the training needs of unregistered care staff have often been neglected, particularly within dementia care provision. The Care Certificate, which was fully launched in in England in April 2015, has aimed to redress this neglect by providing a consistent and transferable approach to the training of the front line health and social care workforce. In order to optimise its impact, the implementation of the Care Certificate is now being evaluated through an 18 month study funded by the Department of Health Policy Research Programme. It is the purpose of this article to outline this evaluation.